MODERN METHODS OF MICROBIOLOGICAL DIAGNOSTICS IN ACUTE TONSILLITIS AND CHRONIC TONSILLITIS EXACERBATIONS IN CHILDREN - V. A Belov (Вопросы современной педиатрии, 2012)
Immunological and microbiological characteristics of chronic tonsillitis in children and various approaches to its treatment are discussed in this article. The principal attention is paid to diagnostics of the main infectious agent — group A -hemolytic streptococci. The study represents a qualitative immunochromatography screening test for the group A streptococci antigens detection — Streptatest. The main principles of rational antibacterial treatment in chronic tonsillitis in children are described.